1992
DOI: 10.1007/bf02759995
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and abuse of psychoactive substances in children and adolescents

Abstract: The present study has been carried out in the slum areas of Gorakhpur city, covering a population of 10,187 in the four colleges of Gorakhpur. Five hundred and eighty children and adolescents in urban slums, and 750 college students between 10-18 years were studied by means of a questionnaire card for detection of prevalence rate and various others co-relates of abuse of psychoactive substances. Overall, prevalence of abuse of psychoactive substances was 25% in slum areas, and 18% in college students. Abuse of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Urban poverty is associated with increased illicit drug use in cities in India [71], Nepal [72] and Brazil [73 -75]. Similar findings have been found in the United States [76 -78].…”
Section: Illicit Drugssupporting
confidence: 77%
“…Urban poverty is associated with increased illicit drug use in cities in India [71], Nepal [72] and Brazil [73 -75]. Similar findings have been found in the United States [76 -78].…”
Section: Illicit Drugssupporting
confidence: 77%
“…Studies on specific disorders [8,28-36], unpublished studies; and studies done on high risk groups [37-43] were not included in this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Out of 28 community based studies one study by Dube et al [44] was excluded as per criteria-2, another one by Hacket et al [45] was excluded as per criteria-4 and 3 studies were excluded as they were done on specific disorders [8,28,29] and another 7 studies were excluded as they were done on high risk groups [37-43]. One study by Lal and Sethi [21] was excluded as per criteria 6.…”
Section: Introductionmentioning
confidence: 99%
“…11 In this subgroup of the population, alcohol use was found in 40% of students, followed by cannabis in 5.4%, opiates (other than heroin) in 1.3% and heroin in 1.1%. 8 Kushwaha et al 12 reported prevalence of psychoactive substance abuse to be 25% in slum areas, and 18% in college students. Abuse of tobacco was most frequent (50.3% and 72.5%) followed by that of alcohol (11.7% and 16.2%) in both the groups respectively.…”
mentioning
confidence: 99%
“…Abuse of tobacco was most frequent (50.3% and 72.5%) followed by that of alcohol (11.7% and 16.2%) in both the groups respectively. 12 A study from New Delhi involving 115 male street children aged 6-16 years reported that more than half of the subjects had indulged in substance use before coming to the observation home. 13 A rise in opiate use was reported in school children.…”
mentioning
confidence: 99%